Hiding in the Pews : Shining Light on Mental Illness in the Church - Austin, Steve (Book collections on Project MUSE., 2021)
In 2012, Steve Austin, then a pastor, nearly died by suicide. His experience launched him on a journey that opened his eyes to the widespread problem of mental illness and how those who live with it are often treated in congregations. He began to wonder: if church folks had talked openly about mental health, therapy, suicide prevention, recovery from abuse, and other difficult issues, would that have changed his story? In Hiding in the Pews, people with mental illness--some of whom might be pastors themselves--will find comfort as they learn they are not alone. Those who know someone with mental illness will gain wisdom about how to be a safe presence. Those who hold the most power in church communities--pastors, board members, and lay leaders--will be challenged and equipped to transform their congregations into places of healing, where it is safe for people to be vulnerable about their suffering. Austin draws on his own experience, as well as on interviews with eighty current and former church leaders and members. Each chapter covers a topic or theme about mental illness and the church and includes practical applications to guide leaders on a journey toward transforming church culture. When a church champions vulnerability and establishes safety within its walls, especially for those who are suffering, the healing power of God can set the captives free. Austin offers hope that faith communities will be the first places people think of when they need a sense of safety and belonging.